(untitled) - 1951-; Ludlum, Robert; 1967-; Akinnouye-Agbaje, Adewale; 1946-; Cox, Brian; Cooper, Chris; 1927-2001.; 1974-; Potente, Franka (Universal City, California, 2002)
Bourne is a spy who has amnesia; other agents are trying to track him down & he is at a loss to know who or what it is all about - all he really knows is that his life is in danger.
Keywords: Spies; Drama; Amnesia; Drama